Diagnosis and treatment of Eagle’s syndrome and possible complications - Kozakovičová, Veronika; Onderka, Arnošt; Res, Oldřich; Stránský, Jiří; Kondé, Adéla; Štembírek, Jan (Acta chirurgiae plasticae, 2023)
Background: Eagle’s syndrome (ES) is a term describing a group of symptoms associated with the elongation of the styloid process (SP) of the temporal bone or with ossification of the stylohyoid ligament. Clinically, it manifests through pain in the orofacial and pharyngeal regions, similar to that experienced by patients with temporomandibular joint disease. The presented paper aims to assess the evaluation of the success of surgical treatment and the complications associated with such treatment. Methods: Our retrospective study includes nine patients with ES treated in our Department Oral and Maxillofacial Surgery in years 2019–2023 (median age of 47 years) – all patients affected with this disease out of 2,716 patients examined at our department due to a temporomandibular joint disease. Eight of these patients underwent a surgical resection of the SP. The success and complications in these patients are evaluated in this study. Results: In seven patients, the problems disappeared or at least diminished, which is consistent with data from the literature. Postoperative complications such as deficit of the marginal branch of the facial nerve (n. VII), limited sticking the tongue out (n. XII), and velopharyngeal insufficiency (n. IX) occurred in three patients. Conclusion: The wide spectrum of clinical manifestations makes ES a condition that should be considered in the differential diagnosis of temporomandibular joint disorders, post-traumatic conditions, or complicated eruption of wisdom teeth or their extraction. ES can be treated conservatively or (mostly) surgically. Surgical treatment can be relatively successful and effective, but it is necessary to respect the anatomical placement of the SP, which can be associated with the development of complications, especially in cases with extremely long SP.
Keywords: Temporomandibular Joint Disorders; Facial Pain; lidé středního věku; Ossification, Heterotopic; spánková kost; lidé; retrospektivní studie; obličejová bolest; heterotopická osifikace; Retrospective Studies; Temporal Bone; Middle Aged; nemoci temporomandibulárního kloubu; Humans